The Tempe Production Training As a Means Woman's Empowerment in Amparaan Village - Mohammad Lutfianto; Fahmi Assulthoni; Ahmad Bahruddin; Muhmmad Nawawi; Mashuri Mashuri; Syaifulloh Arif (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
The community of Amparaan Village faces complex economic challenges, including limited access to nutritious food, high unemployment, low entrepreneurial skills, and minimal knowledge of local food processing conditions that directly undermine family nutrition and household economic stability. Women, as primary household managers, hold a strategic role in local economic empowerment. This study aimed to enhance women's knowledge, skills, and entrepreneurial spirit in tempeh production through Participatory Action Research (PAR), which actively involved 60 participants in training, skills development, and reflective processes. The results demonstrate a significant improvement in participants' capacity: after training, 21 participants (35%) were able to produce tempeh independently, while 37 others (62%) could do so with assistance compared to zero participants with such capability prior to the intervention. Participants' entrepreneurial motivation also increased markedly, indicating strong potential for sustainable, locally-based food enterprises that can positively impact family nutrition and household economic welfare.